2022
DOI: 10.1039/d2sc03511a
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation between 3D and 2D aromaticity: does it really exist? The case of carborane-fused heterocycles

Abstract: Although several synthesized icosahedral carborane fused 2D π-ring systems are known, and even considerable conjugation has been noted between them in some cases, the phenomenon itself is not fully understood....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…Once this takes place, the scaffolding of the o ‐carborane is unblocked, eliminating the C=C and therefore generating a non‐aromatic cyclic system and an aromatic cluster. Therefore, a full 3D/2D aromatic system can never occur, in contradiction to the recently reported experimental results of 3D/2D bonding [7,19a] . Thus we have studied again what could be the causes of the misinterpretation of the NICS and ASE in the o ‐carborane‐fused carbo‐ and heterocycles.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Once this takes place, the scaffolding of the o ‐carborane is unblocked, eliminating the C=C and therefore generating a non‐aromatic cyclic system and an aromatic cluster. Therefore, a full 3D/2D aromatic system can never occur, in contradiction to the recently reported experimental results of 3D/2D bonding [7,19a] . Thus we have studied again what could be the causes of the misinterpretation of the NICS and ASE in the o ‐carborane‐fused carbo‐ and heterocycles.…”
Section: Resultscontrasting
confidence: 66%
“…The latter is indicated in italics in the following pages in order to maintain the nomenclature adopted so far with respect to o‐ benzyne, but we will finally prove that it is in fact a carborene. Earlier work has already shown that 3D aromaticity does not match 2D aromaticity [2d,7] . And, why is that?…”
Section: Introductionmentioning
confidence: 96%
“…In addition to being computationally more challenging, excited-state (anti-)aromaticity also comes with the alert that aromaticity in an excited state is not necessarily Baird aromaticity; there are molecules which are Hückel aromatic in their excited states, [56][57][58] and there are those with excited states that are Hückel-and Baird-aromatic hybrids. [50,51] Finally, similar to the hexagonal hydrogen-bonded (HF) 3 trimer, some transition-metal cycles and carborane-fused heterocycles in the S 0 state, [59][60][61][62] one can encounter situations in excited states where negative NICS values are found in the center of rings without diatropic ring currents. Instead, localized circulations at the edges, or paratropic ring currents in adjacent rings, can lead to a negative NICS value in a certain ring.…”
Section: Henrik Ottosson Received His Phd In 1996 (University Of Goth...mentioning
confidence: 99%
“…Noticeably, the computed AICD plots allow us to observe how the ring current of this newly formed ring is interrupted (Figure and Figure S27). Thus, the hypothesized 2D–3D global aromaticity of these compounds does not take place but aromaticity is localized on the 3D carborane and on the 2D pyridyl ring, not on the intermediate-fused six-membered ring. ,, Then, what is the reason for the distinct NMR properties of these systems? In particular, what is the origin of the unprecedented 1 H NMR chemical shift of 7.46 ppm for the H atom of the fused six-membered ring δ­(H*) of 3c ?…”
Section: Resultsmentioning
confidence: 99%